Customer satisfaction and perception towards the service provided at Tenaga Nasional Berhad Distribution Tampin / Norafidah Ambia - Ambia, Norafidah (Faculty of Business and Manangement, 2001)
The customer satisfaction and perception towards the service provided at TNB were studied at Tenaga Nasional Berhad main office Tampin. The study is important to see the level of customer satisfaction and the customer perception towards services provided at TNB Tampin. The data were gained through the interviews and questionnaires that distributed to the respondents. According to Mr. Shanker Rahman, the Business District Manager, TNBD Tampin had rarely received serious complaints towards the service provided at TNBD Tampin. The sample that chosen manage to contributed good information in this research from the feedback of the respondents, this research identified that 96% of the respondents satisfied with the counter service and electricity service, 98% satisfied with the meter reader service and 940/0 satisfied with Kedai Tenaga service. Customers also give good perception towards the service, provided at TNBD Tampin. The data were presented in the form of tabulations, graphs and charts to make it clear and easy to understand. However this research manage to reveal the level of customers satisfaction and perception towards the service provided at TNBD Tampin. In fact there were still small weaknesses in TNBD Tampin and the management team always attempts to improve its performance. Therefore it is important for TNBD Tampin to find ways to enhance its service quality. For example this organization can use the flowchart as the guideline for the workers in accomplishing their daily task. Motivation can also use to encourage workers to enhance their quality of work. As Malaysia's main electricity supply, utility, TNB must always tries to fulfill the customers satisfaction and show good image to other service organization.